PENGARUH PENAMBAHAN DAN PERLAKUAN PENYIAPAN RECLAIMED ASPHALT PAVEMENT (RAP) TERHADAP KARAKTERISTIK - Suwarto, Fardzanela; Setiadji, Bagus Hario; Supriyono, Supriyono (Civil Infrastructure Engineering and Architectural Design, 2018)
Abstract: The addition of the Reclaimed Asphalt Pavement (RAP) is done by stripping the asphalt mixture on the pavement structure and destroying it into a grained material. The percentage of RAP material addition and treatment of RAP material prior to use as a Job Mix Formula will affect the final result of the asphalt mixture so that the relationship between the asphalt mixture characteristics with the RAP material and the relationship between the asphalt mixture characteristics between the two treatments against RAP with or without the granulator need to be studied. The results of this study show that the addition of RAP material can improve the stability of the asphalt mixture, the optimal value of RAP material addition is between 20% and 30%. In addition, the use of RAP by granulisation process in aggregate mixtures can help to improve stability and mixed stiffness.Keyword: RAP, Asphalt mixture, granulator